Strategy for Diversifying Revenue for The Sustainability of Msmes Pertubuhan Masyarakat Indonesia (Permai) in Penang, Malaysia. - Siswanti, Indra; Nawangsari, Lenny C; Pratama, Aditya (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
The sustainability of Indonesian Micro, Small, and Medium Enterprises (MSMEs) operating abroad hinges on their ability to adapt to dynamic global markets. Revenue diversification has emerged as a critical strategy for mitigating risks and ensuring business resilience. This study highlights the importance of diversification in response to the unique challenges faced by MSMEs abroad, such as market volatility, regulatory differences, and cultural disparities. It identifies three primary strategies for revenue diversification: product diversification, market expansion, and digital transformation. Product diversification allows MSMEs to develop new offerings tailored to local market needs, while market expansion enables entry into new customer segments and geographic regions. Digital transformation facilitates broader market access through e-commerce platforms and online marketing. The study also emphasizes the vital role of stakeholders, including government bodies, financial institutions, and industry associations, in supporting revenue diversification efforts. Policy support, access to finance, and capacity-building initiatives empower MSMEs to strengthen their market presence and achieve sustainable growth. By implementing these strategies, Indonesian MSMEs can enhance their global competitiveness, reduce dependency on single revenue streams, and create a more resilient business model. This research underscores the need for a holistic approach to diversification, involving strategic planning, innovation, and collaboration with key stakeholders. The findings contribute to the discourse on sustainable business practices and offer practical insights for policymakers, business owners, and researchers interested in advancing the global competitiveness of Indonesian MSMEs.